국가 농산물 품질관리의 소비자 후생효과 분석 - 권오상; 김한호; 이문호; 이승호; 이홍림; 한미진 (농촌경제, 2017)
Our study estimates consumer`s willingness to pay for the public services on food safety management and regulation conducted by the National Agricultural Products Quality Management Service (NAQS) of Korea. The WTPs for the three main programs, food safety inspection and regulation, country of origin la-belling management, and certification of environment-friendly agro-fishery prod-ucts and good agricultural practices (GAP), are estimated based on the choice experiments designed to incorporate observed real market data. It is shown that the WTP for each program far exceeds its management cost. Food safety in-spection and regulation and country of origin labelling management showed WTP estimates much larger than the certification program. Moreover, it is found that raising the market share of GAP through the certification system may en-hance consumer welfare because the estimated consumer preference for GAP was very high compared to the current market share of GAP.